Tumour necrosis factor α and nuclear factor κB inhibit transcription of human TFF3 encoding a gastrointestinal healing peptide. Issue 9 (11th August 2003) - Loncar, M B; Al-azzeh, E-d; Sommer, P S M; Marinovic, M; Schmehl, K; Kruschewski, M; Blin, N; Stohwasser, R; Gött, P; Kayademir, T
Abstract : Background and aims: Tumour necrosis factor α (TNF-α) induction of nuclear factor κB (NFκB) activation plays a major role in the pathogenesis of inflammatory bowel disease (IBD). Trefoil factor family peptides TFF1, TFF2, and TFF3 exert protective, curative, and tumour suppressive functions in the gastrointestinal tract. In this study, we investigated effects of the TNF-α/NFκB regulatory pathway by TNF-α on expression of TFFs. Methods: After TNF-α stimulation, expression of TFF genes was analysed by quantitative real time polymerase chain reaction and by reporter gene assays in the gastrointestinal tumour cell lines HT-29 and KATO III. Additionally, NFκB subunits and a constitutive repressive form of inhibitory factor κB (IκB) were transiently coexpressed. In vivo, morphological changes and expression of TFF3, mucins, and NFκB were monitored by immunohistochemistry in a rat model of 2, 4, 6-trinitrobenzene sulphonic acid induced colitis. Results: TNF-α stimulation evoked up to 10-fold reduction of TFF3 expression in the colon tumour cell line HT-29. Downregulation of reporter gene transcription of TFF3 was observed with both TNF-α and NFκB, and was reversible by IκB. In vivo, the increase in epithelial expression of NFκB coincided with reduced TFF3 expression during the acute phase of experimental colitis. Conclusions: Downregulation of intestinal trefoil factor TFF3 is caused by repression of transcription through TNF-α and NFκB activation in vitro. In IBD, perpetual activation of NFκB activity may contribute to ulceration and decreased wound healing through reduced TFF3.